Early Seeds of Bioregionalism: Place-Consciousness and Harmony in Andrew Marvell’s “The Garden” - Frederick , Suresh; Moses , J. Edwin (Journal of Ecohumanism, 2024)
Bioregionalism as a philosophy of ‘living in place’melds issues of social and economic justice and sustainability with cultural, ecological and spiritual concerns.This article examines Andrew Marvell’s “The Garden” through the lens of bioregionalism, arguing that the poem articulates key tenets of this environmental philosophy centuries before its formal emergence. While not explicitly bioregional, Marvell’s work reveals a profound sense of place, emphasising the speaker’s interconnectedness with the garden’s ecosystem. Through vivid sensory detail and the speaker’s physical immersion in the natural world, the poem establishes the garden as a site of profound harmony, where human experience is deeply intertwined with natural rhythms. This article explores how Marvell constructs a sense of place that moves beyond mere observation to embody a reciprocal relationship between individual and environment. Furthermore, it analyses the poem's treatment of solitude, suggesting that while the garden offers solace, Marvell recognizes the limits of complete isolation, hinting at the necessary balance between individual retreat and communal belonging within a bioregion. By examining “The Garden”’s engagement with themes of place-consciousness, interconnectedness, and the cyclical nature of time, this article uncovers early seeds of bioregional thought, revealing how Marvell's work anticipates key concerns of harmonious human-nature relationships that resonate deeply with contemporary environmental discourse.